PENERAPAN AUDIT OPERASIONAL DALAM RANGKA EFEKTIVITAS, EFISIENSI DAN EKONOMIS PENGELOLAAN SEDIAAN CV. LIPI GADING DI BALI - Erlin Tirta Winata; Stevanus Hadi Darmadji (CALYPTRA, 2018)
Abstract - Tourism is one of the fastest growing economic sectors, marked by international tourist arrivals and incomes. The development of tourism makes the art of handicrafts also growing because many tourist arrivals from different countries. This study aims to improve understanding about implementation of operational audit in order to effectiveness, efficiency and economics inventory management CV. Lipi Gading in Bali. This research uses qualitative descriptive research paradigm with data collected using interview method, observation and document analysis. The result in this study shows there are some problems encountered such as bad consignment systems, absence of stock card on finished goods, poor storage of intermediate goods, forecasting errors in purchasing imported stocks, delays in delivering goods and the occurrence of natural disasters. The existence of operational audit aims to assess the performance of the company in inventory management activities in order to effectiveness, efficiency and economics, so that companies can make improvement to improve performance and strategic decision making.